Liver X Receptor alpha Mediated Genistein Induction of Human Dehydroepiandrosterone Sulfotransferase (hSULT2A1) in Hep G2 Cells - Chen, Yue (2013)
Cytosolic sulfotransferases are one of the major families of phase II drug metabolizing enzymes. Sulfotransferase-catalyzed sulfonation regulates hormone activities, metabolizes drugs, detoxifies xenobiotics, and bioactivates carcinogens. Human dehydroepiandrosterone sulfotransferase (hSULT2A1) plays important biological roles by sulfating endogenous hydroxysteroids and exogenous xenobiotics. Genistein, mainly existing in soy food products, is a naturally occurring phytoestrogen with both chemopreventive and chemotherapeutic potential. Our previous studies have shown that genistein significantly induces hSULT2A1 in Hep G2 and Caco-2 cells. In this study, we investigated the roles of liver X receptor (LXRα) in the genistein induction of hSULT2A1. LXRs have been shown to induce expression of mouse Sult2a9 and hSULT2A1 gene. Our results demonstrate that LXRα mediates the genistein induction of hSULT2A1, supported by Western blot analysis results, hSULT2A1 promoter driven luciferase reporter gene assay results, and mRNA interference results. Chromatin immunoprecipitation (ChIP) assay results demonstrate that genistein increase the recruitment of hLXRα binding to the hSULT2A1 promoter. These results suggest that hLXRα plays an important role in the hSULT2A1 gene regulation. The biological functions of phytoestrogens may partially relate to their induction activity toward hydroxysteroid SULT.